The Significance of Teacher Mastery of Student Psychology in Teaching and Learning Process - Husnul Khatimah; Aslin Antonius (Newinera Publisher, 2020)
This study discusses teacher mastery of students psychology in Learning process. Forms of the Student's (spiritual) Psychological Aspects Intelligence/level of Student Intelligence is the ability to react / adapt to the environment student attitude It is a tendency to respond in a relatively constant manner to all objects of people, goods, etc, both positively and negatively. The Role of teachers in fostering student Psychology important psychological factor in achieving learning success, every prospective teacher/professional teacher needs to have knowledge and understanding of intelligence so that they can understand the level of intelligence of their students. it can be interpreted that the role of the teacher in coaching students' psychology which includes internal aspects (intelligence, talents, attitudes, interests and motivation) as well as external aspects of students are very important.